Characteristics of Islam and Political Power in The Sumatran Kingdoms - Ahmad Syaikhu; Rifqi Rifqi (Lentera Demokrasi: Jurnal Ilmu Sosial, Politik, Hukum, Ekonomi dan Pemerintahan, 2025)
Islam in the Nusantara has a close connection with its history of arrival and spread, including its role in the political sphere during the era of the sultanates, particularly in the Sumatra region. This paper discusses the characteristics of Islam and its influence in shaping political power during that period. The study begins by tracing the early history of Islam’s arrival in the Nusantara, which remains a topic of debate among historians. Initially, Islam appeared as small communities in coastal areas, driven by trade, maritime activities, and the spread of Islamic teachings (dakwah). These communities later developed into centers of political power, such as the Sultanate of Aceh, with significant influence on intellectualism and the international dissemination of Islam. The formation of Islamic communities in the Nusantara, particularly in coastal areas, marked the early stages of Islam’s development in the region. According to Taufik Abdullah et al. in *Sejarah Umat Islam Indonesia* (*The History of Islam in Indonesia*), between the 1st and 5th century Hijri (7th to 13th century CE), Muslim traders and preachers played an essential role in introducing Islam through communities amidst the maritime hegemony of Sriwijaya and the Hindu-Buddhist cultural setting. These communities eventually evolved into Islamic centers of power, such as Aceh in Sumatra; Demak, Pajang, and Mataram in Java; Gowa-Tallo and Bone in Sulawesi; and Ternate and Tidore in Maluku. The spread of Islam in the Nusantara is inseparable from the political dynamics, power structures, and political traditions of each kingdom. Besides religious motivations, political and economic interests also influenced the patterns of Islam’s dissemination and the formation of Islamic societies. In the political realm, Islam was initially used to strengthen the position of Islamic kingdoms in facing threats from non-Islamic powers, such as the Portuguese and the Dutch East India Company (VOC), which sought to monopolize maritime trade. Thus, Islam not only became a religious identity but also an essential tool in building political and economic power in the Nusantara.